2020
DOI: 10.1111/exd.14102
|View full text |Cite
|
Sign up to set email alerts
|

Integrin αvβ3‐Akt signalling plays a role in radioresistance of melanoma

Abstract: Melanoma is a deadly type of skin cancer that is particularly difficult to treat owing to its resistance to radiation therapy. Here, we attempted to determine the key proteins responsible for melanoma radioresistance, with the aim of improving disease response to radiation therapy. Two melanoma cell lines, SK‐Mel5 and SK‐Mel28, with different radiosensitivities were analysed via RNA‐Seq (Quant‐Seq) and target proteins with higher abundance in the more radioresistant cell line, SK‐Mel28, identified. Among these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…CLG can also promote the detachment of glioblastoma and mesothelioma cells from ECM components through exposed RGD sequences, resulting in anoikis-dependent apoptosis and inhibition of invasion (32). Notably, as an avb3 integrin-specific inhibitor, CLG also shows encouraging outcomes in pancreatic cells, gliomas, and some metastatic solid tumors, according to some clinical trials (33)(34)(35). However, a further large clinical study indicated that adding CLG to temozolomide chemoradiotherapy does not improve outcomes (36).…”
Section: Discussionmentioning
confidence: 99%
“…CLG can also promote the detachment of glioblastoma and mesothelioma cells from ECM components through exposed RGD sequences, resulting in anoikis-dependent apoptosis and inhibition of invasion (32). Notably, as an avb3 integrin-specific inhibitor, CLG also shows encouraging outcomes in pancreatic cells, gliomas, and some metastatic solid tumors, according to some clinical trials (33)(34)(35). However, a further large clinical study indicated that adding CLG to temozolomide chemoradiotherapy does not improve outcomes (36).…”
Section: Discussionmentioning
confidence: 99%
“…Microarray analysis of two melanoma cell lines, SK-Mel5 and SK-Mel28, with different radiosensitivities, was employed to identify target proteins enriched in the more radioresistant cell line, SK-Mel28, among which integrin avb3 adhesion molecule as well as Akt, were found to contribute to radioresistance, supporting the therapeutic potential of targeting these molecules [79].…”
Section: Protein Kinase Signaling Pathways Role In Melanoma Resistanc...mentioning
confidence: 96%
“…Premature senescence seems to be also induced in normal human fibroblasts as a result of chronic low dose rate (LDR) exposure (5 or 15 mGy/h) of gamma rays ( Fujimori et al, 2005 ). In addition to inducing premature cellular senescence, exposing CAFs to RT results in the potent induction of multiple DNA damage response (DDR) foci as well as the inhibition of the proliferative, migrative, and invasive capacity of these fibroblasts ( Goel et al, 2013 ; Li et al, 2018 ; Im et al, 2020 ). Senescent CAFs have been described to present a senescence-associated secretory phenotype that is characterized by the upregulation and secretion of various substances (e.g., CXCL12, TGF-β1, IGF-1, IGFBP2, and NO) ( Li et al, 2016 ; Ansems and Span, 2020 ), some of which are pro-tumorigenic factors, such as IL-6, IL-8, and osteopontin, and are linked to stroma-mediated therapeutic resistance ( Krisnawan et al, 2020 ).…”
Section: The Effects Of Cancer Therapies On Cancer-associated Fibroblastsmentioning
confidence: 99%